JEWISH SUFISM IN MEDIEVAL ISLAM - Leonard C. Epafras (Universitas Gadjah Mada, 2011)
This article is a literary research and preliminary examination to a unique interaction between Jews and Sufism that taken place in medieval Islamic ruling. In the face of the present antagonistic posture of Jews and Muslims relationship that dominates the public sphere, in history, there are some examples of interaction of the two people beyond confictual narrative. One of them is Jewish mysticism that adopted Sufism into their spiritual ideal, which took place in the medieval era. We might call the phenomenon tentatively as “Jewish Sufism.”